Alkali pretreatment and enzymatic saccharification of blue-green alga Nostochopsis lobatus for bioethanol production - Pradechboon, Thunvarat; Pattranan Junluthin (Maejo International Journal of Energy and Environmental Communication, 2022)
Using various Sodium hydroxide (NaOH) concentrations (0, 1, 2, and 3%), we studied the alkaline pretreatment of microalgal biomass from the blue-green alga Nostochopsis lobatus in this work. In this pretreatment stage, the entrapped polysaccharides found within the microalgae cell walls are broken down to form fermentable subunits. The selected pretreatment procedure (2% NaOH) was then followed by enzymatic saccharification for the generation of bioethanol. This pretreatment step aims to release and break down entrapped polysaccharides in the microalgae cell walls into fermentable subunits. The best result of sugars after enzyme hydrolysis was obtained in total and reducing sugars 210.22 and 98.54 g/L, respectively. In addition, Saccharomyces cerevisiae was used to ferment the hydrolysate; the highest ethanol yield was 14 g/L by 48 hours of fermentation. The alkaline pretreatment method was a promising option for pretreating microalgal biomass for bioethanol production.